Adaptive modulation approaches parameters effect on LTE uplink waveform - D. Aljanabi, Haider; B. Qas Elias, Bashar; D. Aljanabi, Hussam (International Journal of Engineering and Technology, 2018)
The next generation are regarding radio applied sciences designed in conformity with increase the capability and velocity about cellular networks. LTE is the first science designed bluntly because the Next Generation Network NGN yet is embarking in conformity with come to be the de-facto (NGN) mobile get entry to network standards. It takes competencies of (NGN's) services in imitation of grant an always-on cellular information ride same after wired networks. In this paper LTE uplink waveforms displayed with various duplexing mode, Allocated Resources Blocks ARB, Modulation types and total information per frame, QPSK and 16 QAM used as modulation techniques and tested under AWGN and Rayleigh channels, similarity and interference of the generated waveforms tested using auto-correlation and cross-correlation respectively.Â Â